2016
DOI: 10.1111/ajt.13644
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class II Antibody Activation of Endothelial Cells Promotes Th17 and Disrupts Regulatory T Lymphocyte Expansion

Abstract: Kidney transplantation is the most successful treatment option for patients with end-stage renal disease, and chronic antibody-mediated rejection is the principal cause of allograft loss. Predictive factors for chronic rejection include high levels of HLA alloantibodies (particularly HLA class II) and activation of graft endothelial cells (ECs). The mechanistic basis for this association is unresolved. We used an experimental model of HLA-DR antibody stimulation of microvascular ECs to examine the mechanisms u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(118 citation statements)
references
References 48 publications
3
114
0
1
Order By: Relevance
“…Alongside CDC and ADCC classical antibody-induced mechanisms, the relevance of antibody-induced HLA signaling in transplantation has been demonstrated1353. While HLA molecules are principally viewed as antigen presenting structures they are also bona fide signal transduction receptors54.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside CDC and ADCC classical antibody-induced mechanisms, the relevance of antibody-induced HLA signaling in transplantation has been demonstrated1353. While HLA molecules are principally viewed as antigen presenting structures they are also bona fide signal transduction receptors54.…”
Section: Discussionmentioning
confidence: 99%
“…This is a significant gap in our knowledge, since numerous studies have found a strong relationship between DSAs against HLA-DQ and chronic rejection. Exposure of HLA-DR-expressing endothelial cells increased ERK and Akt phosphorylation (153), as well as activation of proinflammatory Th17 cells (154). More studies are needed to elucidate the effect of antibodies against HLA II on vascular endothelial cell signaling, and how they contribute to acute and chronic AMR.…”
Section: Microvascular Inflammation and Endothelial Injurymentioning
confidence: 99%
“…Anti-HLA-DR antibodies can increase EC secretion of IL-6, thereby amplifying a pro-inflammatory response by enhancing T H 17 expansion diminishing functional regulatory T cell (T reg ) proliferation (55). While classically DSA targets have been anti-HLA antibodies, the presence of non-HLA antibodies is increasingly being recognized as correlated with chronic rejection and diminished long-term graft survival (56).…”
Section: The Roles Of Adaptive Immune Cells In Avmentioning
confidence: 99%